MENGENALKAN PEMIKIRAN PIERRE BOURDIEU UNTUK SASTRA ELLY PRIHASTI WURIYANI - Elly Prihasti Wuriyani (Universitas Negeri Medan, 2020)
Abstract Pierre Bourdieu's thought has become an alternative to analyzing the battles waged by the author in the process of ideas, writing, to publication. This reason becomes the basis and consideration that literary studies can enter many domains, not only in literary works but also in authors, society and publishing. Pierre Bourdieu offers the concepts of habitus, capital, realm, and practice. The description method and application method are used to understand Pierre Bourdieu's concept of thought and application to continue the literary work. The result was that Lena Simanjuntak fought in her OBPdPD so she could do shows from 2013 to 2017. Keywords: battle, Perre Bourdiau, Literature, Writer